Rational Emotive Behaviour Psychotherapy and Depressive Behaviour Among Secondary School Adolescents - Muraina Kamilu Olanrewaju; Saleh Musa; Wasilatu Saleh Mamud (Indonesian Journal of Community and Special Needs Education, 2023)
The study was designed to examine rational emotive behaviour psychotherapy and depressive behaviour among secondary school adolescents in Yobe State, Nigeria. A simple random sampling technique was used to select 30 students for the study. The sample participants consist of 15 male and 15 female students. All selected samples were subjected to experimental. The quasi-experimental research design was used in the study. Beck’s Depressive Behavior Inventory (BDI) was administered to assess depressive behaviour before and after the intervention with a 0.85 reliability coefficient. Rational emotive behaviour psychotherapy (REBP) was employed as the treatment for the experimental group. t-test statistical tools using (SPSS) were used to test the 3 hypotheses formulated. The result revealed that REBP was significantly effective in depressive behaviour; the difference in the depressive behaviour was significant for Gender but not for age. Because of these findings, the study recommended that students should be trained on the effective usage of this intervention in REBP. Experts in educational counselling psychologists should intensify their effort to organize seminars/conferences on the implications of this intervention.